1991
DOI: 10.1055/s-2006-960079
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic, Antipyretic and Anti-Inflammatory Properties ofEuphorbia hirta

Abstract: Lyophilised aqueous extract of Euphorbia hirta L. (Euphorbiaceae) has been evaluated for analgesic, antipyretic and anti-inflammatory properties in mice and rats, in order to complete its activity profile, after the confirmation of the existence of a central depressant activity particularly expressed by a strong sedative effect, associated with anxiolytic effects. This study leads us to the conclusion that this plant extract exerts central analgesic properties. Such a dose-dependent action was obtained against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(108 citation statements)
references
References 1 publication
1
103
0
Order By: Relevance
“…In this work, paw volume determinations were the average value of three repeated measures. Percentage of oedema development inhibition was expressed using the following equation: % oedema development inhibition = [(Vt -V0) control -(Vt -V0)treated]/ (Vt -V0) × 100, where Vt is the average paw volumes for each group and V0 average paw volumes for each group prior to treatments, according to Lanhers et al (1991).…”
Section: Methodsmentioning
confidence: 99%
“…In this work, paw volume determinations were the average value of three repeated measures. Percentage of oedema development inhibition was expressed using the following equation: % oedema development inhibition = [(Vt -V0) control -(Vt -V0)treated]/ (Vt -V0) × 100, where Vt is the average paw volumes for each group and V0 average paw volumes for each group prior to treatments, according to Lanhers et al (1991).…”
Section: Methodsmentioning
confidence: 99%
“…We introduced a slight modification to the hot plate test described by Langers et al [14]. In a preselection test, mice were screened by placing the animals onto hot plate (Socrel ® DS-37) setting at 55 ± 0.2 °C and those who failed to lick their hind paw or jump (nociceptive responses) within 10 s were discarded.…”
Section: Hot Plate Testmentioning
confidence: 99%
“…Thirty minutes after treatment, mice were placed individually on the hot plate and the reaction time was again recorded at 0.5, 1 and 2 h after administration of different treatments. In order to minimize damage to the animal's paw, the cut-off time for latency of response was taken as 20 s [14]. The percentage of analgesic activity was calculated as Eq.…”
Section: Hot Plate Testmentioning
confidence: 99%
“…[11,12] In addition, studies by our research group have also shown that the aqueous extract of the plant possesses antioxidant, bronchodilatory, and antimutagenic activities. [13,14] Besides, it exhibits the ability to inhibit production of matrix metalloproteinase (MMP)-13, a potent matrix degradative enzyme involved in OA that cleaves type II collagen.…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%